Tīhei mauri ora: honouring our voices: mana wahine as a kaupapa Māori: theoretical framework - Pihama, Leonie (University of Auckland, 2001)

Local Maori development and government policies - Kawharu, Merata (Social Policy Journal of New Zealand, 2001)

Nation building & Māori development in the 21st century: conference proceedings, 30th August to 1st September 2000. - University of Waikato School of Māori and Pacific Development (School of Māori and Pacific Development, The University of Waikato, 2001)
Keywords: economic conditions; government; māori development; self-determination; sovereignty

Governance and Legitimacy: Indigenous Development in Aotearoa - Dodd, Materoa (He Puna Korero: Journal of Maori & Pacific Development, 2001)
Keywords: hapū; iwi; mana wāhine; post-settlement (waitangi tribunal); rangatiratanga; sexism; tiriti o waitangi/treaty of waitangi

An Exquisite Politeness: The Royal Commission on Genetic Modification and the Redefining of the Treaty of Waitangi - Jackson, Moana (2001)
Keywords: marginalisation; tiriti o waitangi/treaty of waitangi

Māori education and principles of self-determination in the twenty-first century. - O’Sullivan, Dominic (Waikato Journal of Education, 2001)
This paper argues that self-determination to the greatest extent possible is a legitimate aspiration for Maori people. It is argued that in education this requires a philosophical and policy response more focused on Maori autonomy than can be provided within the bicultural framework that has lately informed Maori relationships with other actors in the education arena. The paper considers the place of kohanga reo, kura kaupapa Maori and wananga in relation to broader Maori aspirations for self-determination and discusses proposals that these aspirations be furthered through the establishment of a Maori Education Authority. It is also argued that opportunities for self-determination in New Zealand are compromised by the government's unwillingness to alter a tightly controlled centralised education market to provide genuine Māori autonomy over what type of education might be available and to what end.
Keywords: crown policy; education; rangatiratanga; self-determination

Contested Realities: Race, Gender and Public Policy in Aotearoa/New Zealand - McIntosh, Tracey (2001)
Keywords: discrimination; mana wāhine